2021
DOI: 10.1007/s10877-021-00724-x
|View full text |Cite
|
Sign up to set email alerts
|

Alarms in a neurocritical care unit: a prospective study

Abstract: The contemporary practice of monitoring physiologic parameters in the critical care setting is based on alarm systems with high sensitivity but low specificity. A natural consequence of this approach is a massive amount of alarms, which potentially leads to fatigue in the personnel and negatively impacts the quality of care provided. The study objective is to determine the prevalence, types, and determinants of alarms in a neurological critical care unit (NCCU) prototype. During a one-month period correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Another ICU study found Sp o 2 generated 15% of all alarms, with only 1.4% of those alarms requiring prescriber intervention (23). In another study, only 2.5% of Sp o 2 alarms required physician involvement (24). Others have found up to 93% of postoperative Sp o 2 alarms to be false with poor correlation to measurements of ventilation (3, 25–27).…”
Section: Pulse Oximeters Have Accuracy Issues and Generate Too Many F...mentioning
confidence: 99%
“…Another ICU study found Sp o 2 generated 15% of all alarms, with only 1.4% of those alarms requiring prescriber intervention (23). In another study, only 2.5% of Sp o 2 alarms required physician involvement (24). Others have found up to 93% of postoperative Sp o 2 alarms to be false with poor correlation to measurements of ventilation (3, 25–27).…”
Section: Pulse Oximeters Have Accuracy Issues and Generate Too Many F...mentioning
confidence: 99%
“…In the neurological critical care unit (NCCU), Unal et al (102) used statistical techniques to determine the prevalence, types, and determinants of alarms. Liu et al (103) conducted a study in 2020 on armpit temperature monitoring using an AI-enabled wireless, non-invasive armpit thermometer called iThermonitor.…”
Section: Category I: Monitoringmentioning
confidence: 99%
“…This group needs specific care and constant surveillance by the multiprofessional health team in the hospital environment, to avoid further aggravations and secondary injuries. The execution of this care at the ICU level can be implemented by the nursing team, having as an instrument the systematization of nursing care ( de Arruda et al, 2019 ; Unal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%